Flos Lonicera Combined with Metformin Ameliorates Hepatosteatosis and Glucose Intolerance in Association with Gut Microbiota Modulation - Shin, Na R.; Bose, Shambhunath; Wang, Jing-Hua; Ansari, AbuZar; Lim, Soo-Kyoung; Chin, Young-won; Choi, Han-seok; Kim, Hojun (Frontiers in Microbiology, 2017)
The gut microbiota is important in energy contribution, metabolism and immune modulation, and compositional disruption of the gut microbiota population is closely associated with chronic metabolic diseases like type 2 diabetes (T2D) and non-alcoholic fatty liver disease (NAFLD). Metformin (MET) and Flos Lonicera (FL) are common treatments for metabolic diseases in Western and Oriental medicine. We evaluated the effect of treatment with FL and MET in combination on hepatosteatosis, glucose tolerance, and gut microbiota composition. FL and MET were administered to OLETF rats, an animal model of genetic T2D and NAFLD. The FL+MET treatment reduced liver weight, serum cholesterol, insulin resistance and hepatic MDA level and modulated the gut microbial composition. More specifically, the genera of Prevotella and Lactobacillus were negatively associated with the body and liver weight, hepatic TG and TC content, and serum insulin level. However, the relative abundance of these genera decreased in response to the FL+MET treatment. Interestingly, pathway prediction data revealed that the FL+MET treatment attenuated lipopolysaccharide-related pathways in keeping with the decrease in serum and fecal endotoxin level. FL and MET in combination exerts a synergistic effect on the improvement of hepatosteatosis and insulin sensitivity in OLETF rats via modulation of gut microbiota.